Interest Rates Targeting of Monetary Policy: An Open Economy SVAR Study of Malaysia - Zulkefly Abdul Karim; Bakri Abdul Karim (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
This paper examines the implementation of monetary policy during the interest rates targeting in a small-open economy (i.e. Malaysia) by using an open-economy structural VAR (SVAR) study. It tests the effect of foreign shocks upon domestic macroeconomic fluctuations and monetary policy, and examines how effective monetary policy is in influencing macroeconomic variables. The results show that during interest rates targeting, monetary policy plays a significant role in affecting macroeconomics variables. This finding suggests that monetary policy has an important role as a stabilization policy in a small-open economy.